Silicato de cálcio como indutor de tolerância ao déficit hídrico em plantas - Nascimento, Alex Favaro (2013)
Two big hindrances that limit the production of foods in Brazil and mainly on the North Estate of Espirito Santo: the elevated acidity of the soil and the long periods of drought causing hydric deficit. Some alternatives are used to contour these problems, like the rectification of the soils, in the acidity case; and the genetic improvement, cultural practices respecting the agricultural climate zoning and the practice of irrigation, in the hydric deficit case. The calcium silicate as agricultural corrective is becoming the promising practice due specially to the low cost. Thus, the objective of this work was to evaluate the potential of development of tolerance to the drought in the cultures of conillon coffee, papaya and brachiaria, as the soil correction with calcium silicate. The experiment was conducted in casa-de-vegetação of CEUNES, in São Mateus-ES. There were evaluated, singly, three plants species: Conillon coffee, Brachiaria and papaya. It was used the simple factorial scheme 4x3, being 4 levels of hydric deficit and 3 levels of agricultural correctives, in randomized blocks, with three repetitions. There were accomplished agronomic assessments, physiological, anatomical and chemical of the soil and plant. To the coffee culture, a tendency is observed to the increase of plants’ height with the usage of the calcium silicate, also causing reduction of the gaseous changes of these plants. Yet, the papaya plants drastically suffered with the levels of hydric deficit observing the reduction in the height values of the plants, diameter of the lap and IFA. The brachiaria didn’t suffer a lot of interference of the correctives, neither from the levels of hydric deficit, being observed statistic differences only for MSF and MST. So, we can say that the calcium silicate conceivably causes tolerance to the drought in the studied cultures, needing more studies to the embodiment of this fact.